Pengaruh Firm Size dan Komite Audit Terhadap Internet Financial Reporting dengan Profitabilitas Sebagai Variabel Intervening - Tri Maryani; Abdul Aziz Nugraha Pratama (MALIA: Journal of Islamic Banking and Finance, 2021)
The purpose of this study is to find out and analyze the Influence of Firm Size and Audit Committee on Internet Financial Reporting with Profitability as a Variable Intervening Case Study on Sharia Commercial Banks Period 2014-2020. This type of research is quantitative research using secondary data. The population in this study was 14 sharia commercial banks, using purposive sampling techniques obtained samples of 10 sharia commercial banks.. The results of this study showed that Firm Size and Profitability had a positive and significant influence on IFR, while the Audit Committee had a positive and insignificant effect on IFR. The Firm size and Audit Committee have a positive and insignificant effect on Profitability. Based on the analysis of the path, variable profitability is not able to mediate the influence of Firm Size and the Audit Committee on IFR.